COVID-19 vaccine hesitancy and acceptance among the public in the Gulf Cooperation Council countries: A review of the literature - Muath A. Alsalloum; Yusuf M. Garwan; Jimmy Jose; Abrar K. Thabit; Nour Baghdady (Taylor & Francis Group, 2022)
Vaccine hesitancy has a significant impact on tackling infectious diseases as it has resulted in reemergence of vaccine-preventable diseases. This review aims to provide an up-to-date evaluation of COVID-19 vaccine hesitancy among the public in the Gulf Cooperation Council countries. We searched the PubMed and SCOPUS databases for manuscripts published on vaccine hesitancy and/or acceptance among the public in GCC countries up till April 1st, 2022. Forty-nine studies met the inclusion criteria and were reviewed. The average vaccine hesitancy rate across GCC countries was 43%. Concerns about vaccine safety (n = 32) and effectiveness (n = 26) were most frequently associated with hesitancy. Being male (n = 25) and having positive behavior regarding the influenza vaccine or vaccines in general (n = 22) were most frequently associated with acceptance. Collaborative efforts of governments, academic bodies, and the media to provide evidence of vaccines' effectiveness throughout history and strictly manage the spread of the vaccine safety-related rumors are warranted.